Characteristics of raw and cooked fillets in species of actual and potential interest for Italian aquaculture Rainbow trout (Oncorhynchus mykiss) and meagre (Argyrosomus regius) - Martelli, Roberta (Premio Tesi di Dottorato, 2014)
Heat treatment generally induces structural changes of fish muscle and loss of nutrients. Depending on many intrinsic and extrinsic factors farmed fish qualitative attributes can be subject to changes. The aim of this study was to assess the effects of boiling on physical parameters and nutritional profile of fillets from two farmed species [meagre (Argyrosomus regius) and rainbow trout (Onchorynchus mykiss)]. Specie-specific differences in physico-chemical traits influenced raw flesh quality and the response to cooking. In meagre, sampling times differences in macronutrients were nullified by cooking. In rainbow trout, boiling modified physico-chemical profile depending on the strain while farming conditions affected cooked fillet quality in a different extent according to the strain.